Monilethrix: A report of three cases in children confirmed with dermoscopy - Remya R Rajamohanan; Biswanath Behera; Prabhakaran Nagendran; Munisamy Malathi (Wolters Kluwer Medknow Publications, 2020)
Monilethrix is a rare hereditary disorder affecting hair resulting in hair fragility and alopecia. We report three patients of monilethrix who presented with complaints of sparse and brittle hair from early childhood. All three patients had multiple discrete hyperkeratotic papules over the scalp. Dermoscopy revealed beaded appearance of hair with the presence of elliptical nodes and intermittent constrictions on the hair shafts as well as broken hairs, which were confirmed with routine microscopic examination of hair. Dermoscopy helps in easier and faster diagnosis of monilethrix.